1974
DOI: 10.1113/jphysiol.1974.sp010683
|View full text |Cite
|
Sign up to set email alerts
|

The absorption of 125I‐labelled immunoglobulin G by different regions of the gut in young rats

Abstract: SUMMARY1. 125I-labelled homologous IgG was injected into different regions of the small intestine of rats aged 12, 16, 18, 20 and 22 days. At 12 days the proximal and middle regions of the intestine readily absorbed globulin and transmitted it to the circulation. The distal region of the intestine transmitted little to the circulation at all ages tested.2. The intestine loses its ability to transmit globulin to the circulation in a distal-proximal direction. At 16 and 18 days the ability of the middle region h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 15 publications
(16 reference statements)
1
38
1
Order By: Relevance
“…All of these products were cleared rapidly from the circulation. In order to account for the very low levels of radioactivity present in the sera of animals sampled 1 hr after the injection of labelled immunoglobulin G into the ileum (Morris & Morris, 1974), it was suggested that immunoglobulin G, like polyvinyl pyrrolidone (Clarke & Hardy, 1969) might be taken up and accumulated in the large supranuclear vacuole, present in the ileal absorptive cells. Our present results show that this suggestion is invalid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these products were cleared rapidly from the circulation. In order to account for the very low levels of radioactivity present in the sera of animals sampled 1 hr after the injection of labelled immunoglobulin G into the ileum (Morris & Morris, 1974), it was suggested that immunoglobulin G, like polyvinyl pyrrolidone (Clarke & Hardy, 1969) might be taken up and accumulated in the large supranuclear vacuole, present in the ileal absorptive cells. Our present results show that this suggestion is invalid.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure followed has been described in detail elsewhere (Morris & Morris, 1974). The labelled preparation contained 5 mg immunoglobulin G/ml.…”
Section: Preparation Of Labelled Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…T h e p e r s o r p t i o n o f macromolecules such as LF and IgG in animal intestines ceases after gut closure [7,28,29], however, it has been reported that LF is persorbed from the intestinal lumen into the blood circulation [13,24,38], and that food antigens and their immune complexes are also persorbed from the intestine into the peripheral blood in adult humans [8,18]. In a previous study, we suggested that luminal bovine serum albumin (BSA) antigen is persorbed by villous columnar epithelial cells at the late apoptotic stage, being mediated by the specific antibody (SpAb) in orally immunized juvenile rats.…”
mentioning
confidence: 99%
“…Like the pig, these neonates internalize macromolecules nonselectively (8). However, unlike the pig, nonselective internalization occurs from mid-gut to ileum only (9,10). These neonates, again unlike the pig, selectively transport immunoglobulin-G from the upper gut only.…”
mentioning
confidence: 89%